Strategic business models: opportunities for business model innovation in the automotive industry - evaluation of car subscription models and development of recommendations - Schmidt, Maximilian Joshua (2022)
Digitization and changing customer preferences have an impact on the determinants of sales and ownership in the automotive industry. In this context it is crucial to understand the new, disruptive business models and their potential for market players. The purpose of this report is to evaluate different business models that exist in the automotive industry in Germany and develop recommendations for improving key components of the recently emerged business model of car subscriptions, wherein a customer gains access to a car in return for a flat rate in the medium-term without the transfer of legal ownership